Penerapan Metode Simple Additive Weighting (SAW) Dalam Sistem Pendukung Keputusan Pemilihan Calon Peserta Pelatihan Kepemimpinan Pengawas Bagi Pejabat Struktural - Sri Lestari; Yomi Kusumah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In the nomination of candidates for Pelatihan Kepemimpinan Pengawas (PKP), the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Bekasi is still experiencing problems in determining the nominative to be dispatched. The impact of these problems is in the form of a mismatch of the nominations of potential participants with priorities that must be expedited. Therefore, it is necessary to have a system that uses a database so as to assist the leadership in making decisions to determine and determine the nominative priorities of prospective PKP participants. In this study, the authors propose the application of the Simple Additive Weighting (SAW) method. The data collection method used is the method of observation and interviews. The criteria proposed from the interview results include Age (weight: 0.35), Echelon (weight: 0.25), Group (weight: 0.2), Service Period (weight: 0.15) and Employee Work Target Value (weight: 0.05). The system development method used is the Waterfall method. The system is built using the PHP programming language with MySQL as the database. System design using Unified Modeling Language (UML) and system testing using Black-box Testing. With this decision support system, the leadership will get the results of anyone who has the right to be proposed to take part in the Training.